THE PERFORMANCE OF RELIGIOUS TEACHERS AT ISLAMIC HIGH SCHOOL IN NUNUKAN ISLAND, NORTH KALIMANTAN - Hasnah Hasnah (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims at determining the performance of religious education teachers in Aliyah Madrasas on Nunukan Island, North Kalimantan, and increasing the role of performance of religious education teachers in carrying out their duties to Aliyah Madrasas on Nunukan Island, North Kalimantan. This type of research is qualitative research located on Nunukan Island, North Kalimantan. Methods of data collection are carried out using observation, interview and documentation techniques. Data analysis carried out was data reduction, data presentation and data verification. Then the data validity is tested by observation and triangulation.The results showed that performance of religious education teachers in the Aliyah Madrasah on Nunukan Island in North Kalimantan is relatively good. However, it still needs to be improved, especially in terms of discipline, ability in the preparation of components of learning devices, as well as the ability to use learning media. 2) Teacher education strategies to improve their performance by conducting continuous evaluations, supervising and evaluating administration, 3) Supporting factors for the performance of religious education teachers, namely a conducive learning atmosphere, harmonious relationships, the ability of the headmaster to motivate teachers. While the inhibiting factors are the lack of facilities and infrastructure needed by religious education teachers, small and minimal income.